The effectiveness of the exoneration clause in the terms and conditions (Terms of Service) of the E-Commerce platform on the Protection of Digital Consumer Rights - Mahliyanti Adelia Warman; Gokma Toni Parlindungan S; Amanda Bherlyana Putri (CV Edujavare Publishing, 2026)
The effectiveness of the exoneration clause in the terms and conditions (Terms of Service) of the E-Commerce platform on the Protection of Digital Consumer Rights